(untitled) (Journal of Bio-Science, 2024)
Amaranthus spp. are widely consumed as vegetables for their nutritious qualities and also have applications in traditional medicine. The current research attempts to identify the phytochemicals, cytotoxicity effects, and antioxidant activities of the stem of A. tricolor, A. blitum, A. viridis, and A. spinosus. The stem powder was extracted by solvent using methanol, ethanol, and aqueous. The methods were used for phytochemical screening (standard protocol), total phenol content (Folin-ciocalteau assay), total flavonoid content (aluminum colorimetric assay), cytotoxicity (brine shrimp lethality assay) and antioxidants (phosphomolybdate and DPPH assay). The phytochemical analysis revealed the existence of alkaloids, flavonoids, terpenoids, carbohydrate, glycosides, c. glycosides, amino acids, xanthoproteins, phenols, saponins, steroids, and coumarins. Among the four species, the methanolic extracts of A. blitum showed maximum quantities of phenol (20.02 ± 0.32 mg GAE/g), flavonoid (27.76 ± 0.29 mg QE/g) and high antioxidant activity (IC50 = 103.25 ± 1.52 µg/ml). The highest total antioxidant capacity was observed in the ethanolic extract of A. viridis (48.53 ± 2.98 mg AA/g). The stem of A. blitum showed little cytotoxic impact (LC50 <1000) and the rest of the species were non-cytotoxic (LC50>1000). The findings demonstrated that the selected Amaranthus spp. are a valuable source of phytochemicals and natural antioxidants. This research suggests conducting further investigation to detect novel compounds. J. Bio-Sci. 32(1): 57-67, 2024